1999
DOI: 10.1016/s0092-8674(00)81656-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferases Dnmt3a and Dnmt3b Are Essential for De Novo Methylation and Mammalian Development

Abstract: The establishment of DNA methylation patterns requires de novo methylation that occurs predominantly during early development and gametogenesis in mice. Here we demonstrate that two recently identified DNA methyltransferases, Dnmt3a and Dnmt3b, are essential for de novo methylation and for mouse development. Inactivation of both genes by gene targeting blocks de novo methylation in ES cells and early embryos, but it has no effect on maintenance of imprinted methylation patterns. Dnmt3a and Dnmt3b also exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

117
4,279
5
52

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 5,343 publications
(4,516 citation statements)
references
References 41 publications
117
4,279
5
52
Order By: Relevance
“…The latter lacks catalytic activity (Denis et al, 2011). The most abundant of these is DNMT1, which is primarily responsible for maintenance and regulation of DNA methylation patterns, while DNMT3A and DNMT3B establish de novo methylation patterns which are then maintained by DNMT1 (Jones and Baylin, 2002;Okano et al, 1999). Previous studies have shown that significant increased expression of DNMT1 protein positively correlates with the hypermethylation status of CpG islands of several genes in gastric cancers, including p16, human MutL homologue 1 (hMLH1), CDH1, and thrombospondin-1 (THBS1) (Etoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The latter lacks catalytic activity (Denis et al, 2011). The most abundant of these is DNMT1, which is primarily responsible for maintenance and regulation of DNA methylation patterns, while DNMT3A and DNMT3B establish de novo methylation patterns which are then maintained by DNMT1 (Jones and Baylin, 2002;Okano et al, 1999). Previous studies have shown that significant increased expression of DNMT1 protein positively correlates with the hypermethylation status of CpG islands of several genes in gastric cancers, including p16, human MutL homologue 1 (hMLH1), CDH1, and thrombospondin-1 (THBS1) (Etoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1 functions primarily in maintenance methylation during DNA replication using hemimethylated DNA as substrates (Lyko et al, 1999;Robertson et al, 1999;Rountee et al, 2000;Robert et al, 2003;Suzuki et al, 2004). The reactions of de novo methylation using unmethylated DNA are thought to be primarily catalysed by DNMT3A and DNMT3B in mammals during early development (Okano et al, 1999;Bachman et al, 2001;Brueckner and Lyko, 2004;Hermann et al, 2004;Dodge et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is involved in gene silencing, switching and stabilizing, and chromatin remodeling (Okano et al, 1999;Li, 2002). In mammals, DNA methylation is known to be reprogrammed on a genome-wide level in germ cells and in preimplantation embryos, although it is relatively stable in somatic cells (Reik et al, 2001).…”
Section: Introductionmentioning
confidence: 99%